Toward sustainability and resilience with Industry 4.0 and Industry 5.0 - Aheleroff, Shohin; Huang, Huiyue; Xu, Xun; Zhong, Ray Y. (Frontiers in Manufacturing Technology, 2022)
There is a recognized need for mass personalization under sustainability transition. Mass personalization is becoming a leading research trend in the latest Industrial Revolution, while substantial research has been undertaken on the role of Industry 4.0 enabling technologies. The world is moving beyond mass customization, while manufacturing has led to mass personalization ahead of other industries. However, most studies have not treated human capabilities with technologies and machines as a sustainable collaboration. The principal objective of this research is to investigate mass personalization as a common goal under Industry 4.0 and Industry 5.0 and propose a reference architecture for achieving human-centric mass personalization that contributes to understanding how Industry 5.0 enhances Industry 4.0 for higher resilience and sustainability through a human-centric approach. The study implies that Human Capital 5.0 leads collaboration with machines and technologies, bringing more value-added and sustainable products.